Uso de vincristina por vía subcutánea y endovenosa en el tratamiento de tumor venéreo transmisible en perros - Guerrero Santacruz, Tobias (2019)
The present work is the result of a comparative study between two routes of ad- ministration for the treatment of transmissible venereal tumor (TVT)., Ten dogs that came to consultation to the Veterinary Teaching Hospital were sampled. For each in- dividual, a clinical sheet was made and samples of the bloody secretion of the tumor were collected, which were then taken to the laboratory for their respective analysis. The systemic effect was compared with two routes of administration of vincristine. In five patients it was put the subcutaneous route (SC) with a dose of 0.025mg / kg of vincristine diluted in 3ml of 0.9 % sodium chloride, every 7 days in the dog’s upper rib cage. Likewise, in 5 individuals it was applied IV administration with the same dose of vincristine described above, prior to the application of a drug protocol to res- tore the patient (0.9 % sodium chloride serum every 7 days) . It was proved that the SC route is viable and offered efficacy in the remission of the tumor in 5 patients. There was no statistical difference in the duration of treatment in the comparison of the two routes (p-value = 0.6265). , The route Ev had an average of 3.6 applications and 32.2 days while; the Sc route an average of 4.2 applications, with 32.6 days. In relation to costs, the Sc route was cheaper than the Ev route, with costs of $ 9.80 (Sc) and $ 21.19 (Ev) for each session; in this study the costs for the 5 patients treated by route Sc was $ 148.40 and Ev $ 404.44.It is concluded that vincristine was effective by SC route for the treatment of TVT with economical benefits and safety in patients, including geriatric and decayed patiens. Key words: Dogs, chemotherapy, sarcoma, neoplasia, TVT, vincristine.